DECONSTRUCTING STUDENT NEEDS IN EAP FOR STEM: INSIGHTS FROM BALEAP 2023 SYMPOSIUM (BALEAP Journal of Research and Practice, 2025)
The BALEAP STEM SIG 2023 Symposium on 'Deconstructing student needs in EAP for STEM' provided insights into the unique challenges and strategies for teaching English for Academic Purposes (EAP) in science, technology, engineering, and mathematics (STEM) disciplines. Key presentations included Natasha Rust's emphasis on integrating register, genre, and discourse analysis into EAP for science courses, Sanchia Rodrigues's exploration of mathematical proficiency and discourse in EAP for maths, and Aaron Woodcock and Lori-Ann Milln's strategies for creating sustainable English for Specific Academic Purposes (ESAP) curricula focusing on vocabulary, speaking, mediation skills, and reflection. Audience discussions highlighted the need for flexible teaching approaches to cater to diverse STEM student groups and the importance of embedding EAP within the broader academic framework. The symposium underscored the collaborative nature of developing effective EAP programs that address both language and subject-specific needs, ensuring the preparation of students for academic success in their respective STEM fields. This interactive infographic and symposium write-up aims to summarise the presentations and discussion at the symposium, to foster ongoing discussions and developments in EAP for STEM education.